We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
94
1
avatar

(2x+1)/(x)+(4x)/(2x+1)=5

 Feb 11, 2019
 #1
avatar+18458 
+1

Multiply both sides of the equation by (2x+1)  to get

 

(2x+1)^2/x + 4x = 10x+5       now multiply by x

(2x+1)^2 + 4x^2 = 10x^2 + 5x     expand left side

4x^2 + 4x + 1   +  4x^2 = 10x^2 + 5x          collect like terms,,,,,and subtract   10x^2 and 5x from both sides

 

-2x^2 - x +1  = 0

2x^2+x-1 = 0

(2x - 1)( x + 1) = 0      x= 1/2    or  -1  

 Feb 11, 2019

7 Online Users

avatar